2022
DOI: 10.3389/ijph.2022.1604341
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sustainable Development Goals Accelerators With Adolescents’ Well-Being According to Head-of-Household’s Disability Status–A Cross-Sectional Study From Zambia

Abstract: Objectives: We examined associations between accelerators (interventions impacting ≥2 SDG targets) and SDG-aligned well-being indicators among adolescents 16–24 years old in Zambia.Methods: We surveyed adults from 1,800 randomly sampled households receiving social cash transfers. We examined associations between accelerators (social cash transfers, life-long learning, mobile phone access) and seven well-being indicators among adolescents using multivariate logistic regressions.Results: The sample comprised 1,7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…Our data clearly show that different outcomes may require different combinations of protective factors, which is in accordance with what has been found in previous accelerator studies [e.g., 8,11,17,28]. The pattern emerging from the current data seems to suggest that two to three protective factors can often provide a substantial boost, while additional factors provide for marginal gain and diminishing returns.…”
Section: Plos Onesupporting
confidence: 92%
“…Our data clearly show that different outcomes may require different combinations of protective factors, which is in accordance with what has been found in previous accelerator studies [e.g., 8,11,17,28]. The pattern emerging from the current data seems to suggest that two to three protective factors can often provide a substantial boost, while additional factors provide for marginal gain and diminishing returns.…”
Section: Plos Onesupporting
confidence: 92%
“…Since then, Hub researchers have identified accelerators across the region, clarifying the concept and enhancing the evidence base. Examples include: in Malawi and South Africa, food security, safe communities, and government cash transfers improved adolescents' physical growth, mental health, and educational outcomes (H. ; in Ethiopia, government sexual and reproductive health and rights (SRHR) education reduced child marriage and adolescent pregnancy and improved educational outcomes (W. E. ; in Zambia, cash transfer, learning and mobile phone access reduced poverty and disability health restrictions and improved educational outcomes for adolescents in disability-affected families (Chipanta et al, 2022).…”
Section: Accelerator Concepts -A Boosted Paradigmmentioning
confidence: 99%
“…In Zambia, a major study on young people living in disability-affected households identified important impacts of social protection and mobile phone access on this under-researched group (Chipanta et al, 2022).…”
Section: Science For Policy Impactmentioning
confidence: 99%
“…To our knowledge, the current study makes the first attempt to measure two unexplored dimensions of ontological security (violence and mental health), aligning them with SDG targets. Second, most studies focusing on accelerators used cross-sectional data and longitudinal data up to two time points (Chipanta et al, 2022;Cluver et al, 2019;Haag et al, 2022;Mebrahtu et al, 2021;Meinck et al, 2021). The current study is one of the first accelerator research using data from three time points, which could pose essential understanding of the long-term effects of consistent exposure to accelerators, enhancing their potential to be considered protective factors (Rudgard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%